Rotifer diversity of fish ponds manured with livestock waste - Francis, T; Ramanathan, N; Athithan, S; Rani, P Rosalind Daisy; Padmavathi, P (Indian Journal of Fisheries, 2011)
The present paper deals with the rotifer diversity in fish ponds manured withanimal waste (poultry excreta, cow dung, cow liquid manure and pig waste)Thirty nine species were recorded from all the four ponds out of which 33 were rotifers. Pig waste manured pond showed the highest species diversity with a total of 30 species followed by cow dung manured pond with 24 species. Brachionus was represented by 17 species with the maximum of 13 species in pig waste manured pond. B. calyciflorus, B. diversicornis, B. caudatus, F. longiseta, A. intermedia and copepods were common in all the ponds, whereas rare species like B. calyciflorus v. hymani and B. havensis were reported only from cattle liquid manured pond